Strategies to measure progress and productivity in model-based construction projects - Ahmad Atif, Adzman (2019)
These days more construction projects arise and to ensure the efficiency of these projects, precise construction progress measurement is needed. Current manual progress and productivity tracking are very time consuming and have a high possibility for error to occur. As we are advancing towards modern construction projects, we require tools and techniques in ensuring accurate progress measurement. Nowadays we have model-based technologies to assist in measuring those progress. However, current literature does not provide with proper strategies on how to benefit the model in measuring progress nor productivity. This study explores the current and potential strategies to measure progress using model-based technology. Qualitative data from individual interviews with industry practitioners that have experienced with model-based construction projects were analysed. It can be said most of the companies in construction industry prefer the real-time construction simulation. The findings of the study will add to the current literature by providing the strategy of progress measurement in model-based construction.